(untitled) (Cultura Económica, 2025)
The thesis of this essay suggests to acknowledge one of the difficulties of artificial intelligence in its attempt to surpass human intelligence. This difficulty is centered on the question of metaphor as a manifestation of an embodied mind. The essay starts from the observation of a kind of anthropological dualism underlying the mentality of the pioneers of artificial intelligence in the 1970s, according to the testimony and interviews conducted by MIT researcher Sherry Turkle. Then follows closely the theorization of metaphor by the cognitive linguistics of Georges Lakoff and Mark Johnson. This essay draws on the techno-optimism and techno-gloom of the thought of contemporary philosophers Andy Clark and Eric Sadin and the inescapable thought of Martin Heidegger.